Rancangan Sistem Informasi Pemesanan Barang Menggunakan Ecommerce Pada PT Trivia Nusantara - Alya Meidina Azzahra (Applied Business and Administration Journal, 2023)
Information system for ordering goods based on e-commerce is a system used to make goods ordering transactions using online-based media. This design aims to facilitate ordering goods for customers, as well as convenience for companies. This is one of the solutions to overcome errors in managing goods orders to customers. This allows businesses to easily enter purchase data without writing notes or sales books. Enable store owners to review sales data quickly and efficiently. This study aims to create a more effective means of buying and selling compared to previous methods at PT Trivia Nusantara. This design is done using data flow diagrams in the form of easy-to-create process flows.